Human leukocyte antigens antibodies after lung transplantation: Primary results of the HALT study. Issue 9 (15th May 2018) - Hachem, Ramsey R.; Kamoun, Malek; Budev, Marie M.; Askar, Medhat; Ahya, Vivek N.; Lee, James C.; Levine, Deborah J.; Pollack, Marilyn S.; Dhillon, Gundeep S.; Weill, David; Schechtman, Kenneth B.; Leard, Lorriana E.; et al.
Abstract : Donor‐specific antibodies (DSA) to mismatched human leukocyte antigens (HLA) are associated with worse outcomes after lung transplantation. To determine the incidence and characteristics of DSA early after lung transplantation, we conducted a prospective multicenter observational study that used standardized treatment and testing protocols. Among 119 transplant recipients, 43 (36%) developed DSA: 6 (14%) developed DSA only to class I HLA, 23 (53%) developed DSA only to class II HLA, and 14 (33%) developed DSA to both class I and class II HLA. The median DSA mean fluorescence intensity (MFI) was 3197. We identified a significant association between the Lung Allocation Score and the development of DSA (HR = 1.02, 95% CI: 1.001‐1.03, P = .047) and a significant association between DSA with an MFI ≥ 3000 and acute cellular rejection (ACR) grade ≥ A2 (HR = 2.11, 95% CI: 1.04‐4.27, P = .039). However, we did not detect an association between DSA and survival. We conclude that DSA occur frequently early after lung transplantation, and most target class II HLA. DSA with an MFI ≥ 3000 have a significant association with ACR. Extended follow‐up is necessary to determine the impact of DSA on other important outcomes. Abstract : In this prospective, multicenter, observational study, the authors report that 36% of lung transplant recipients develop donor‐specific antibodies to human leukocyte antigens within 120 days of transplantation. Snyder and Tinckam's editorial is onpage 2111 .